2022
DOI: 10.1021/acsaem.2c01647
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole-Functionalized Multiquaternary Side-Chain Polyethersulfone Anion-Exchange Membrane for Fuel Cell Applications

Abstract: A series of rPES(x/y)-MI membranes with different rigid side chains and highdensity imidazole cationic groups have been prepared for anion-exchange membrane (AEM) fuel cells (AEMFC). These AEM rPES(x/y)-MIs with IEC values of 1.91−2.31 mequiv g −1 exhibit high conductivities of 92.92−142.69 mS cm −1 at 80 °C, acceptable water uptake, and dimensional change. Density functional theory (DFT) was used to demonstrate the excellent alkali stability of this class of copolymers, which is consistent with experimental r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…As can be seen in Figure S6, the E a of QAPCE-1.4P is 14.44 kJ mol –1 , which suggests that less energy is required for the OH – transportation and a high ion conducting efficiency in QAPCE-1.4P. Furthermore, a comparison of the OH – conductivity of the as-prepared membranes with other AEMs reported in recent years is presented in Figure b. It can be found that QAPCE-1.4P has a higher OH – conductivity than other membranes in a similar IEC, indicating that the performance of AEMs can be enhanced by improving the phase separation of membranes via adjusting the hydrophilic–hydrophobic polarity. Meanwhile, the complexation of sodium ions and crown ether plays a role as the cationic groups (as confirmed in Figure S3) that is also helpful to enhance the electrochemical behaviors of AEMs.…”
Section: Resultsmentioning
confidence: 63%
“…As can be seen in Figure S6, the E a of QAPCE-1.4P is 14.44 kJ mol –1 , which suggests that less energy is required for the OH – transportation and a high ion conducting efficiency in QAPCE-1.4P. Furthermore, a comparison of the OH – conductivity of the as-prepared membranes with other AEMs reported in recent years is presented in Figure b. It can be found that QAPCE-1.4P has a higher OH – conductivity than other membranes in a similar IEC, indicating that the performance of AEMs can be enhanced by improving the phase separation of membranes via adjusting the hydrophilic–hydrophobic polarity. Meanwhile, the complexation of sodium ions and crown ether plays a role as the cationic groups (as confirmed in Figure S3) that is also helpful to enhance the electrochemical behaviors of AEMs.…”
Section: Resultsmentioning
confidence: 63%
“…Then, the possible degradation mechanism was proposed (Figure S6). It was found that the hydroxide conductivity of ImPSF-PEG200, ImPSF-PEG600, ImPSF-PEG1000, ImPSF-PEG2000, and ImPSF-PEG4000 remained at 59%, 58%, 67%, 71%, and 63% of their original values, respectively, after 360 h (15 days), which showed moderate alkaline stability in comparison to the reported membranes under the same testing conditions [26,[54][55][56][57][58]. In comparison, the ImPSF membrane remained at only 52% of its original value after 360 h, showing that blending with PEG can significantly improve the alkaline stability of AEMs.…”
Section: Alkaline Stabilitymentioning
confidence: 81%
“…Over the last decade, several polyarylene ether (PAE) polymers have been widely adopted as the backbone in AEMs because of their good mechanical properties, film-forming ability, and thermal stability. Many innovative AEMs have been developed based on polymer backbones such as polyether ether ketone, [73,74] polyphenylene oxide (PPO), [75,76] polybenzimidazole, [77,78] and polyethersulfone [79,80] (Figure 4a). Recent reports have revealed that not only cations but also polymer backbones can undergo nucleophilic attack by OH À , resulting in polymer degradation, especially when polar bonds such as ether and sulfone are present in the backbones.…”
Section: Strategies For Polymer Backbonesmentioning
confidence: 99%